Enhancing student well-being: the Impact of a mindfulness-based program (Mind7+) on stress, anxiety, sleep quality, and social Interactions in a sample of portuguese university students - Pinto, Paula (2023)
There is an urgent need to promote mental health strategies in university students, and mindfulness-based interventions provide alternative and complementary approaches. The present study aimed to investigate the impact of a mind-fulness-based program (Mind7+) on Portuguese students from the Polytechnic University of Santarem, focusing on stress levels, depression, anxiety, and sleep quality. The intervention consisted of a 8 week mindfulness-based program, with six presential sessions and two online sessions. The participants completed self-filled validated questionnaires before and after intervention. The study revealed that Mind7+ program not only positively influenced stress levels, anxiety, and sleep quality among university students but also had a positive impact on their social interactions. A correlation between sleep quality and frequency of individual practices was observed. The observed medium effect size under-scores the practical relevance of Mind7+ program and the potential of mindfulness-based interventions in higher education to enhance both individual well-being and social connections.